Analysis of preharvest sprouting in three Brazilian wheat populations - Bassoi, Manoel Carlos; Flintham, John; Riede, Carlos Roberto (Pesquisa Agropecuaria Brasileira, 2006)
The objective of this work was to evaluate the possibility of obtaining recombinant inbred wheat lines more resistant to preharvest sprouting, independently of colour genes, in three red-grained Brazilian wheat populations. The results showed statistical significance among lines within all populations, which presented a normal distribution and transgressive segregation for preharvest sprouting. The normal distribution of the lines from all red-grained populations suggests that sprouting, excluding the genes expressing seed coat pigmentation, is, probably, controlled by many genes. These findings also indicate that it may be possible to improve resistance to preharvest sprouting, independently of the colour genes.